Justice fiscale // Sécurit´de l'emploi // OUI à l'Initiative sur les banques
Finanzwesen;Steuerwesen;Steuerpolitik;Steuerbelastung Finanzwesen;Steuerwesen;Steuerpolitik;Steuerrecht politischer Rahmen;Wahlen und Abstimmungen;Volksabstimmung;Volksinitiative